Historical Dictionary of Singapore - Corfield, Justin (Rowman & Littlefield Publishers, 2010)
In spite of Singapore's small size, it has long had a major impact on the world because of its geographical location and its wealth. The British initially made the island a major port for the shipping of goods and later as an airline hub for the region. These factors, along with a steady government, have helped to contribute to the country's affluence. This multicultural, multiracial, and multi-religious island-nation is the envy of many countries in the world, which have tried to emulate the economic success of Singapore. The new edition of the Historical Dictionary of Singapore has been completely rewritten since the first edition was released 20 years ago. It relates the history of this country through a chronology, an introductory essay, an expansive bibliography, and over 500 cross-referenced dictionary entries on significant persons, events, places, organizations, and other aspects of Singapore history from the earliest times to the present.